Phenolic acid profiles of endemic species Verbascum anisophyllum and Verbascum davidoffii: Phenolic acid profiles of Verbascum species - Nikolova, Milena Tihomirova; Berkov, Strahil; Dimitrova, Marina; Sidjimova, Boryana; Stoyanov, Stoyan; Stanilova, Marina (Journal of BioScience and Biotechnology, 2018)
The profiles of methanol extractable and methanol insoluble bound phenolic acids of two species: Verbascum anisophyllum Murb (Balkan endemic) and Verbascum davidoffii Murb. (Bulgarian endemic) were determined. Free radical scavenging activity and total phenolic content of studied extracts and fractions were evaluated by DPPH antioxidant method and Folin–Ciocalteu reagent, respectively. Phenolic acid profiles were analyzed by GC/MS. Sixteen phenolic acids and their derivatives were detected. Ferulic acid was the major individual phenolic acid presented in all extracts and fractions. Hydroxycinnamic, vanillic and p-hydroxybenzoic acids were also abundant in the studied phenolic acid profiles. The presence of gentisic, syringic, isoferulic, dihydroferulic, eudesmic, 3,5-di-tert-butyl-4-hydroxybenzoic acids were reported for the first time to Verbascum species. The greatest variety of phenolic acids was found in the fractions containing methanol insoluble bound hydrolysable phenolic acids. The highest free radical scavenging activity and total phenolic content were established for methanol extractable alkaline hydrolysable fractions. Phenolic acid profiles and free radical scavenging activity of both species were similar although V. davidoffii contained few more components. The present study is the first report on the phenolic acid profiles and free radical scavenging activity of V. anisophyllum and V. davidoffii as well as first detailed study of the phenolic acid profiles of the Verbacum species.